(Methodological) nationalism and academic debates on the integration of migrant children. (3rd October 2022) - Gornik, Barbara
Abstract: The article takes up current academic debates on the integration of migrant children and reflects on how they accommodate the discourse of nationalism; it discusses how nationalism functions as a practical category, as a classification scheme, and as a cognitive framework, as well as what counter‐hegemonic views can be found in the existing scholarship. The article shows that academic debates about the integration of migrant children are firmly situated on the conceptual map of nationalism, but navigate this field in different ways. Principally, these debates 1) maintain migrant identity as the main analytical category; 2) focus on the gap exhibited by migrant children in various aspects where non‐migrant children are used as the standard of 'normality'; 3) view ethnic diversity as a 'problem' and therefore approach it as something 'pathological'; and 4) examine migrant children in relation to nationalizing practices that touch on issues of identity, language, community, and belonging; yet also 5) offer critical counter‐hegemonic views concerning the integration of migrant children and deconstruct the power relations and commonly held classification schemes within the discourse of nationalism.